APLIKASI DONASI BERBASIS MOBILE MENGGUNAKAN METODE SCRUM - Habibah, Ariska Nurul; Waluyo, Retno; Jefri Prayitno Bangkit Saputra (Yayasan Nusantara Hasana Berdikari, 2024)
The donation application creates innovative solutions in the world of charity and charity with a design that focuses on an immersive user experience. In Indonesia, there are many online donation applications, but most of the donations given are in the form of money. Apart from money, victims of natural disasters also need assistance in the form of primary goods to meet their basic needs. Given these problems, the